2015
DOI: 10.1007/s13201-015-0355-2
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater arsenic and fluoride in Rajnandgaon District, Chhattisgarh, northeastern India

Abstract: The groundwater of Ambagarh Chouki, Rajnandgaon, India, shows elevated levels of As and F-, frequently above the WHO guidelines. In this work, the concentrations of As, F-, Na ? , Mg 2? , Ca 2? , Cl-, SO 4 2-, HCO 3-, Fe, dissolved organic carbon (DOC) and dissolved inorganic carbon (DIC) in the groundwater of Ambagarh Chouki are described. The sources of dissolved components in the groundwater are investigated using the cluster and factor analysis. Five factors have been identified and linked to processes res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…There are many countries around the world like India, China, Mexico, Argentina, and Pakistan, where these contaminants are reported to coexist in groundwater. In India, the co-occurrence of both these contaminants in the groundwater of Rajnandgaon District in the state of Chhattisgarh has been reported to be well above the permissible limits …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…There are many countries around the world like India, China, Mexico, Argentina, and Pakistan, where these contaminants are reported to coexist in groundwater. In India, the co-occurrence of both these contaminants in the groundwater of Rajnandgaon District in the state of Chhattisgarh has been reported to be well above the permissible limits …”
Section: Introductionmentioning
confidence: 98%
“…In India, the co-occurrence of both these contaminants in the groundwater of Rajnandgaon District in the state of Chhattisgarh has been reported to be well above the permissible limits. 8 Co-occurrence of these pollutants may create more serious effects on human health. Various techniques such as ion exchange, reverse osmosis, chemical reduction, electrodialysis, distillation, biological processes, adsorption, and other processes have been investigated by different research groups to remove arsenic and fluoride from water and reported in literature.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies from different parts of the world showed the excess of fluoride in groundwater: Sri Lanka (Dissanayake 1991), Serbia (Mandinic et al 2010), China (Chen et al 2012, Ethiopia and Malawi (Msonda et al 2007). Excessive groundwater fluoride level was also reported in several states of India: Rajasthan (Choubisa 1997), Tamil Nadu (Gopalakrishnan et al 1991), Uttar Pradesh (Jha et al 2010), Bihar (Verma et al 2016, Chhattisgarh (Patel et al 2015) and Haryana (Singh et al 2007;Meenakshi et al2004;Yadav and Lata 2003).…”
Section: Discussionmentioning
confidence: 97%
“…Further, the factor analyses for different variables which were measured from the Chaturangi glacier meltwater for both the years are presented in Table 5. Factor analysis is a useful statistical method that used to explain the relationship between the different analyzed variables by the computation of various multivariate factors and by reducing the complex data to an easily interpretable data (Davis, 2002;Patel et al, 2017). Factor analysis is also called the principal component analysis which is also helpful for the visualization and management of complex system of data, when similarities of data and patterns are not well understood (Valder, Long, Davis, & Kenner, 2012).…”
Section: Discussionmentioning
confidence: 99%